Distribution of Pythium myriotylum Drechsler causing soft rot of ginger - K N Shiva, A Kumar, S T Reeja, R Suseela Bhai (Journal of Spices and Aromatic Crops, 2008)
Fourteen of the 29 Pythium isolates pathogenic to ginger (Zingiber officinale) collected fromvarious parts of India such as Assam, Karnataka, Kerala, Sikkim and Uttar Pradesh wereidentified as Pythium myriotylum based on the size of the species-specific amplicon (150 bp)using the oligo primers Pmy5 and ITS2. The suitability of the primer combination Pmy5 (5’-gTC gCT gTT ATg gCg gAg-3’) and ITS2 (5’-gCT gCg TTC TTC ATC gAT gC-3’) (Wang et al.2003a) at the species level identification of P. myriotylum was further confirmed through thisstudy.